2021
DOI: 10.1007/s10055-021-00604-4
|View full text |Cite
|
Sign up to set email alerts
|

Nature in virtual reality improves mood and reduces stress: evidence from young adults and senior citizens

Abstract: Large populations worldwide have been deprived from nature experiences due to mass quarantines and lockdowns during the COVID-19 pandemic, and face a looming mental health crisis. Virtual reality offers a safe and practical solution to increase nature exposure. This research examined the effects of virtual nature using a within-subject design with young adults (Study 1) and senior citizens (Study 2). Results from the young adult sample showed that walking in a virtual forest reduced negative affect due to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
112
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 100 publications
(115 reference statements)
4
112
1
9
Order By: Relevance
“…Advances within this field allow for creation of 3D models containing representations of nature that can achieve high levels of realism. Studies using this type of VR sceneries in the context of virtual green exercise have reported positive psychophysiological responses as demonstrated by Chan et al ( 2021 ). However, to the best of the authors’ knowledge, only two studies have directly compared 360° videos with matching (or similar) 3D models.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Advances within this field allow for creation of 3D models containing representations of nature that can achieve high levels of realism. Studies using this type of VR sceneries in the context of virtual green exercise have reported positive psychophysiological responses as demonstrated by Chan et al ( 2021 ). However, to the best of the authors’ knowledge, only two studies have directly compared 360° videos with matching (or similar) 3D models.…”
Section: Introductionmentioning
confidence: 75%
“…In the context of virtual green exercise, different types of technology have been used to create virtual representations of natural environments, including computer screens (see, e.g., Akers et al 2012 ; Mayer et al 2009 ; Pretty et al 2005 ; White et al 2015 ) and head-mounted displays ( HMD; see, e.g., Alkahtani et al 2019 ; Calogiuri et al 2018 ; Chan et al 2021 ). By enclosing the user within the virtual environment and replacing the sensory input from the real surroundings with sensory input from the virtual environment (Slater et al 1995 ), HMDs are believed to be a more efficient tool compared to other displays, as they can provide higher levels of immersion (Joseph et al 2020 ; Litleskare et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gabungan dari ruang virtual berbasis alam untuk tujuan terapi dikenal dengan nama virtual nature (Chan et al, 2021) dengan pendekatan terapi berbasis alam atau biasanya disebut nature assisted therapy (Berger, 2017;Koptyin & Rugh, 2017;Kopytin, 2017). Diketahui terdapat pendekatan lain yang disebut nature assisted education, yaitu pendidikan yang berbasis kepada alam (Febrianto et al, 2021) Penelitian ini berbeda dengan penelitian sebelumnya, karena berusaha menggabungkan bidang arsitektur (unsur lanskap), bidang informatika (virtual reality) dan bidang psikologi (terapi kenyamanan visual).…”
unclassified